HUBUNGAN HALAQAH TARBIYAH DENGAN SELF-REGULATED LEARNING SANTRI DI PONDOK PESANTREN MODERN MUHAMMADIYAH - Naufal Zuhdi 'Afif; Luthfiah Tri Yunita (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study aims to determine the relationship between halaqah tarbiyah and students’ self-regulated learning at Pondok Pesantren Modern Al-Mumtazah Muhammadiyah Ajibarang. This research employed a quantitative approach with a correlational research design. The population consisted of 19 ninth-grade students, and all members of the population were selected as the research sample using a total sampling technique. Data were collected through questionnaires, observation, and documentation. The research instrument used a Likert scale that had been tested for validity and reliability. The reliability test results showed that the halaqah tarbiyah variable obtained a Cronbach’s Alpha value of 0.876, while the self-regulated learning variable obtained 0.900, indicating that both instruments were reliable. Based on the normality test using Shapiro-Wilk, the data were found to be not normally distributed; therefore, hypothesis testing was conducted using the Spearman Rank test. The results showed a significant relationship between halaqah tarbiyah and students’ self-regulated learning with a significance value of 0.001 and a correlation coefficient of 0.678, which falls into the strong category. This study indicates that guidance through halaqah tarbiyah plays an important role in developing students’ self-regulated learning through discipline habituation, self-evaluation, learning guidance, and behavioral control within the boarding school environment.